2012
DOI: 10.1038/tp.2012.31
|View full text |Cite|
|
Sign up to set email alerts
|

Dysregulation of DGCR6 and DGCR6L: psychopathological outcomes in chromosome 22q11.2 deletion syndrome

Abstract: Chromosome 22q11.2 deletion syndrome (22q11DS) is the most common microdeletion syndrome in humans. It is typified by highly variable symptoms, which might be explained by epigenetic regulation of genes in the interval. Using computational algorithms, our laboratory previously predicted that DiGeorge critical region 6 (DGCR6), which lies within the deletion interval, is imprinted in humans. Expression and epigenetic regulation of this gene have not, however, been examined in 22q11DS subjects. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…1A), has been reported to be more variably expressed among 22q11DS subjects, especially on the maternally inherited allele. 30 Interestingly, a significant majority of 22q11 deletions are of maternal origin. 31 Alternatively, some interactions that occur when both alleles are present may occur relatively infrequently, and thus the loss of one allele may reduce the interaction frequency below the level of detection.…”
Section: Discussionmentioning
confidence: 99%
“…1A), has been reported to be more variably expressed among 22q11DS subjects, especially on the maternally inherited allele. 30 Interestingly, a significant majority of 22q11 deletions are of maternal origin. 31 Alternatively, some interactions that occur when both alleles are present may occur relatively infrequently, and thus the loss of one allele may reduce the interaction frequency below the level of detection.…”
Section: Discussionmentioning
confidence: 99%
“…As neural crest cells establish the vasculature of the pharyngeal arch arteries along with the capsule of the thymus, changes in their location would affect the morphogenesis of this region. While the transcript levels of DGCR6 as well as its homolog, DGCR6L should be reduced 50% due to their respective haploinsufficiency in 22q11.2del patients, their levels are extremely variable in 22q11.2del patients (Chakraborty et al, 2012). Some individuals actually have much higher levels of DGCR6 compared to normal controls (Chakraborty et al, 2012).…”
Section: The Genetic and Epigenetic Regulation Coupled To Tbx1 Functionsmentioning
confidence: 98%
“…One is with DiGeorge Critical Region 6 (DGCR6), a gene also encoded on the frequently deleted segment of chromosome 22q11.2. DGCR6 down-regulates TBX1, impacting neural crest migration within the pharyngeal region ( Figure 2, Table 3) (Groot et al, 2004;Chakraborty et al, 2012). As neural crest cells establish the vasculature of the pharyngeal arch arteries along with the capsule of the thymus, changes in their location would affect the morphogenesis of this region.…”
Section: The Genetic and Epigenetic Regulation Coupled To Tbx1 Functionsmentioning
confidence: 99%
“…We identified parent-of-origin studies that met the following criteria: (1) the study detailed parent of origin data for NAHR-mediated loci as designated by Coe et al, 2014 15 , (2) the study reported parent of origin data for non-imprinted loci, (3) the study reported data for more than 10 families with affected children, and (4) the study clearly treated monozygotic twins as one meiosis event. 25 studies met inclusion criteria; from these 25 studies, data were curated for six loci, including copy number variants at 5q35.3 9,36 , 7q11.23 1,7,37-42 , 16p11.2 5 , 17p11.2 [43][44][45] , 17q11.2 8,31,32 , and 22q11.2 6,38,[46][47][48][49][50][51] (Table 1). Each locus has between one and eight independent studies representing in total 1,438 de novo deletion and duplication events.…”
Section: Recurrent Genomic Disorder Loci Literature Searchmentioning
confidence: 99%